PERANCANGAN TERMINAL BUS DI KOTA MALANG JAWA TIMUR DENGAN PENERAPAN ARSITEKTUR METAFORA - Andjasmoro Pangestu; Sri Kurniasih (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2020)
The Bus Station is a road transport infrastructure for the purposes of lowering and raising passengers, moving intra and/or inter modes of transportation, and arranging the arrival and departure of public transportation. The author focuses on the development of Arjosari Terminal located in the Malang city, East Java. The main problem of this terminal is ineffective space circulation patterns and slum. So that, the author will design a new terminal that will replace Arjosari Terminal because it sees a fairly complex problem that is owned by Arjosari Terminal. Metaphor Architecture is an architectural style that takes the form of a figure of speech or parable of some thing. Taking the concept of real objects or values that are commonly known to the public that considered more simple and reasonable. So that the Terminal design in Malang city will use the Metaphor Architecture theme from the shape of the mountain to give the impression and emphasize that Malang city is a city who surrounded by mountains around it.